Possible Mechanisms of Action of an Anti-Pasteurella pestis Factor - Eisler, D. M. (1968)
Anti-Pasteurella pestis factor (APF) inhibited bacterial growth, but there was no evidence that APF from either mouse or guinea pig or selected fatty acids physically disrupted the cell wall. The fatty acids selected were representative of those found in APF. APF inhibited oxidation of β-d-glucose but not oxidation of glucose-6-phosphate, whereas fatty acids inhibited the oxidation of glucose-6-phosphate but not oxidation of β-d-glucose. The oxidation of 6-phosphogluconic acid was inhibited by both APF and free fatty acids. Furthermore, APF and potassium laurate inhibited 6-phosphogluconic dehydrogenase in a cell-free extract of P. pestis strain E.V. 76. No evidence of β-d-glucose or glucose-6-phosphate dehydrogenases was found in the cell-free extract. The results suggested that APF and fatty acids may kill P. pestis by inactivating 6-phosphogluconic acid dehydrogenase. The effects of these agents on other enzyme systems were not excluded.